8. Sınıf Öğrencilerinin Doğal Afet ve Afet Eğitimi Kavramını Anlama Düzeyleri / The Understanding Levels on Natural Disasters and Disasters Education Concepts for 8th Grade Students Students - Karakuş, Ufuk; Önger, Seda (Journal of History Culture and Art Research, 2017)
Abstract Natural disaster is defined as suddenly developing natural or human phenomena that harm human life and natural order. Many natural disasters have occurred in Turkey throughout history, resulting in serious loss of life and property. Although people can not prevent natural disasters, however, they can take various measures to reduce the damages. In order to reduce the indemnities caused by natural disasters, Turkey has taken many precautionary measures especially after 1999 Marmara earthquake. These steps are mostly focused on the formation of disasters, ways to prevent disasters, and legal regulations. This research was conducted to determine the level of understanding of the concept of disaster and disaster education by 8th grade students of middle school. The study sample consists of 8th grade students from Dört Eylül middle school of Simav district, Kütahya province. The research was carried out with 28 middle school students during academic year of 2014-2015. A semi-structured questionnaire consisting of open-ended questions, developed by researchers, was applied as data collection tool. The data of the study were analyzed using qualitative research techniques. Results show that students’ first perception about the word disaster is earthquake disaster, tsunami disaster. Therefore, environmental conditions of an area are found affecting the perception. Besides, variable of gender is also not found affecting the results. However, increase in income level and educational level of parents result difference in answers. Öz Ani gelişen veya ortaya çıktığında kötü sonuçları olan doğal ve beşerî olaylar, insan yaşantısına ve doğal düzene zarar vermekte ve bu durum doğal afet olarak nitelendirilmektedir. Tarih boyunca Türkiye’de pek çok doğal afet meydana gelmiş ve bunların sonucunda ciddi can ve mal kayıpları yaşanmıştır. İnsanlar doğal afetlerin oluşumunu engelleyememelerine rağmen, bunların zararlarının azaltılmasına yönelik çeşitli önlemler alabilirler. Doğal afetlerin meydana getireceği zararları azaltmak için ülkemizde özellikle 1999 Marmara depreminden sonra çalışmalara hız verilmiştir. Bu çalışmalar daha çok afetlerin oluşumu, afetlerden korunma yolları ve yasal düzenlemeler üzerine odaklanmıştır. Bu araştırma, 8. sınıf öğrencilerinin afet ve afet eğitimi kavramı hakkındaki anlama düzeylerini tespit etmek amacıyla gerçekleştirilmiştir. Çalışma grubunu Kütahya İli, Simav ilçesi Dört Eylül Ortaokulu 8. Sınıf öğrencileri oluşturmaktadır. Araştırma, 2014-2015 eğitim-öğretim yılında 8. Sınıfta okuyan 28 ortaokul öğrencisi ile yapılmıştır. Veri toplama aracı olarak, araştırmacılar tarafından geliştirilen açık uçlu sorulardan oluşan yarı yapılandırılmış anket uygulanmıştır. Çalışmanın verileri nitel araştırma teknikleri kullanılarak analiz edilmiştir. Çalışmanın sonucuna göre; öğrencilerin afet deyince ilk olarak deprem afetine, enaz tsunami afetine yer verildiği bulgulardan anlaşılmıştır. Dolayısıyla çevre şartları sonucu etkilemiştir. Genel olarak bakıldığında cinsiyet değişkeni sonucu etkilememiştir. Fakat ailenin gelir durumu ve ailenin eğitim durumu arttıkça afet eğitimi cevaplarında farklılık vardır.